D15 Functional mri signal fluctuations highlight altered resting brain activity in huntington's disease. (13th September 2016) - Salvatore, Elena; Sarappa, Chiara; Filla, Alessandro; Cocozza, Sirio; Russo, Cinzia Valeria; Saccà, Francesco; Brunetti, Arturo; Quarantelli, Mario; Michele, Giuseppe De
Abstract : Background: Brain Resting State Functional Magnetic Resonance Imaging (rsfMRI) may be a useful biomarker to study pathological alterations in Huntington's disease (HD). Among post processing analyses techniques, the fractional Amplitude of Low Frequency Fluctuations (fALFF) and the degree of local synchronisation (Regional Homogeneity – ReHo) of resting-state BOLD signal have been suggested to map the spontaneous neuronal activity and the local functional connectivity (FC), respectively. Few studies explored the relationship of brain function and clinical measures in HD. Aims: To investigate rsfMRI changes in HD mutation carriers, in order to further understand the complex mechanisms underlying HD pathophysiology. Patients and Methods We assessed fALFF and ReHo changes, independent of atrophy, in 11 presymptomatic (ps-HD) and 28 symptomatic (sHD) HD mutation carriers, compared to 40 normal volunteers, and tested possible correlations with the Unified Huntingtont's disease Rating Scale motor and cognitive scores. Results: In sHD patients, fALFF was mainly reduced bilaterally in parietal lobes (right precuneus being already affected in psHD), and superior frontal gyri, and increased bilaterally in cerebellar lobules VI, VIII and IX, and in the right inferior temporal gyrus. ReHo was reduced in sHD, and to a lesser extent in psHD, bilaterally in putamina, cerebellar lobules III to VI, and superior medial frontal gyri, and increased in both psHD and sHD in fronto-basal cortices, and in the right temporal lobe. fALFF correlated inversely with cognitive scores in lobule IX of the cerebellum (mainly with total Stroop score, p < 0.0001), and the medial portions of both thalami. Conclusions: Our results are consistent with a reduced neuronal activity in the cortical components of the executive networks, known to be affected in HD, and a reduced local functional integration in subcortical and cerebellar components of the sensori-motor network. Correlation of fALFF with executive function scores in cerebellar clusters may be related to compensatory mechanisms.